Parents' time with children: micro and macro perspectives - Altintas, E (2013)
This thesis studies the dynamics of parents’ time with children. It uses self-reported time diary data to empirically document discrepancies between high- and low-educated parents’ time spent in various childcare activities. By doing so, the study considers one important but under-researched form of childhood inequality, namely inequality in parental time investment. The thesis is among the first to provide an extensive and detailed empirical documentation of variations in parents’ time use with children and to examine the effect of macro-structure and policy context on parenting behaviour. Using the American Time Use Survey (2003-2008), the thesis first investigates variations in parents’ time spent in different types of childcare among white parents in the US. Then, the American Heritage Time Use Survey (1965-2010) is employed to examine whether differences between high-and low-educated parents’ time spent with children have been growing or diminishing over time. Finally, the Multinational Time Use Survey (1965-2008) is used to explore the relationship between specific policies, macro-economic structure and childcare across time and across countries. The results can be summarized as follows. High-educated parents provide more primary childcare for their children compared to low-educated parents. The difference is particularly acute during the early years of childhood, and the gap is particularly wide for childcare activities which are fundamentally important for the social and cognitive development of children. This parental investment gap, most notably between high-and low-educated mothers, has been widening in the US. The main source of this widening phenomenon is the steady increase in high-educated mothers’ time spent in interactive and developmental childcare activities, rather than in routine and physical childcare activities. The analysis of cross-national data shows that the strong positive effect of education on childcare is a cross-national occurrence. However, the strength of this association varies considerably across time and across countries: universal paid leave for mothers and a gender egalitarian labour market structure help alleviate the education and gender gap in childcare. Mothers provide more primary childcare as the number of available paid leave weeks increases, while fathers increase their contribution to primary childcare as the percentage of women in the labour market increases. The provision of paid leave for mothers decreases the effect of education on primary childcare, and specific family policies as well as gender egalitarian socio-economic contexts can help alleviate inequalities in parental time investment in children.